Sensitivity Determination and Differential Validity in Endurance of Trunk Muscles for Healthy People and Patients with Low Back Pain - Seyyd Mohammad Ebrahim Mousavi; Amir Masoud Arab; Mahyar Salavati (University of Social Welfare and Rehabilitation Sciences, 2005)
Objective: To collectively investigate the several clinical tests have been used to measure endurance of the trunk muscles in subjects with and without low back pain (LBP) and identify the sensitivity of each test to predict the probability of the occurrence of LBP. Testing the spinal muscle endurance seems to be very important in prediction, prevention and rehabilitation of LBP. Several types of methods of static endurance testing such as: Sorensen test, prone isometric chest raise test, prone double straight-leg raise test, Supine isometric chest raise test and Supine double straight-leg raise test, regarding their utilization have been reported in the literature. However, identification of the tests that have more dominant sensitivity on assessment of LBP has not yet been determined. Information regarding the sensitivity of each test is needed for effective prevention and appropriate treatment strategies. Materials & Methods: Total of 200 subjects participated in this study. Subjects were categorized into four groups: asymptomatic males (N = 50, mean age = 38±12 years), asymptomatic females (N= 50, mean age = 43±11 years), males with LBP (N = 50, mean age = 39±12 years), and females with LBP (N = 50, mean age = 43±12 years). Five clinical tests were measured in each group and the relative association of each test with on LBP was assessed. Results: Among all the performed tests, prone double straight-leg raise test had the highest association with LBP. Other tests such as the, Prone isometric chest raise test, Supine isometric chest raise test and Supine double straight-leg raise test had low association with LBP in compare with Prone double straight-leg raise test. Conclusion: It seems that Prone double straight-leg raise test has more association with LBP than other tests and could be used to as an useful method for testing the spinal muscle endurance, prediction of the probability of the occurrence of LBP, prevention and rehabilitation of LBP.